Generating personalized business card designs from images - Antunes, N.; Ferreira, J.; Cardoso, E. (Multimedia Tools and Applications, 2022)
Rising competition in the retail and hospitality sectors, especially in densely populated and touristic destinations is a growing concern for many business owners, who wish to deliver their brand communication strategy to the target audience. Many of these businesses rely on word-of-mouth marketing, delivering business cards to customers. Furthermore, the lack of a dedicated marketing team and budget for brand image consolidation and design creation often limits the brand expansion capability. The purpose of this study is to propose a novel system prototype that can suggest personalized designs for business cards, based on an existing business card picture. Using perspective transformation, text extraction and colour reduction techniques, we were able to obtain features from the original business card image and generate an alternative design, personalized for the end user. We have successfully been able to generate customized business cards for different business types, with textual information and a custom colour palette matching the original submitted image. All of the system modules were demonstrated to have positive results for the test cases and the proposal answered the main research question. Further research and development is required to adapt the current system to other marketing printouts, such as flyers or posters.